ANALISIS BOTTLENECK DAN CHARGING COST PADA PEMBUATAN TIANG PANCANG PT. WIKA BETON PPB BOYOLALI - Angga Dwi Setiawan; Novan Fahlevi; Bambang Riyanto; Rudi Yuniarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
To be competitive in the market competition, then a company is required to be able to work without defects, especially in the production process, especially in terms of time, but in the process of production of the most common problem is the bottleneck. In addition, the process of making the finished product, if the consumer is too long to take the goods orders will certainly lead to additional cost for the manufacturer (PT. WIKA Beton Boyolali). Therefore, it is necessary to charge to cover the cost calculation the amount of cost / additional costs. The purpose and goal of this study was to maximize the production of piling PT. WIKA Beton Boyolali, as well as reducing the amount of losses arising from the cost / surcharge. Bottleneck determination made by the method of calculation of standard time each work station, while charging for the cost calculation performed by three methods: Base On Plan, Mixing Pile, Base On Demand. From the results of the analysis showed that the bottleneck is at the work station spinning, and to reduce the bottleneck distasiun the work can be done by adding the spinning tool and also the addition of workers / operators. While charging the cost of the analysis showed that of the three methods used, the most effective method is a method Charging Cost Base On Mixing Pile. It is expected to cost charging system is then the consumer can pay more attention to pick up their order as soon as possible when the order finished goods.